Correlation of Arterial Stiffness with Left Ventricular Global Longitudinal Strain and Diastolic Function in Hypertensive Patients - Abbas, Ethar Saad; Al-Salihi, Oday J.; Alkaaby, Abdulhadi Hameed (Medical Journal of Babylon, 2025)
Abstract Background: Arterial stiffness is one of the complications of hypertension. It is a hallmark of vascular aging, and when assessed with the carotid-femoral-pulse wave velocity (cf-PWV), it is predictive of outcome regardless of blood pressure components. Objectives: To detect subclinical involvement of left ventricular (LV) systolic and diastolic dysfunction in hypertensive patients in whom arterial stiffness is high. Materials and Methods: A case-control study with 55 randomly taken hypertensive patients aged 30-60 years old (female = 25 and male = 30) was conducted from December 2022 to June 2023. Their findings were contrasted with those of 55 healthy people. The Sample was collected in Marjan Teaching City, Babylon province, Iraq. Arterial stiffness measured by cf-PWV and wide pulse pressure (PP) results in correlation with LV systolic and diastolic function. The LV systolic function was done by measuring global longitudinal strain, and the diastolic function was done according to the new guideline. Results: In comparison to control subjects, hypertensive patients have significant evidence to have subclinical LV systolic dysfunction in whom they have arterial stiffness and demonstrated a strong link (P value <0.001). Conclusion: Arterial stiffness measured by cf-PWV and PP highly correlated with subclinical LV abnormality, and there was no significant relationship between arterial stiffness and diastolic function. Subclinical LV abnormalities and arterial stiffness, as measured by cf-PWV and PP, are highly associated. Arterial stiffness and diastolic function are not significantly correlated.